Autophagy Impairment Is Associated With Increased Inflammasome Activation and Reversal Reaction Development in Multibacillary Leprosy - de Mattos Barbosa, Mayara Garcia; de Andrade Silva, Bruno Jorge; Assis, Tayná Quintella; da Silva Prata, Rhana Berto; Ferreira, Helen; Andrade, Priscila Ribeiro; da Paixão de Oliveira, Jéssica Araújo; Sperandio da Silva, Gilberto Marcelo; da Costa Nery, José Augusto; Sarno, Euzenir Nunes; Pinheiro, Roberta Olmo (Frontiers in Immunology, 2018)
Leprosy reactions are responsible for incapacities in leprosy and represent the major cause of permanent neuropathy. The identification of biomarkers able to identify patients more prone to develop reaction could contribute to adequate clinical management and the prevention of incapacities. Reversal reaction may occur in unstable borderline patients and also in lepromatous patients. To identify biomarker signature profiles related with the reversal reaction onset, multibacillary patients were recruited and classified accordingly the occurrence or not of reversal reaction during or after multidrugtherapy (MDT). Analysis of skin lesion cells at diagnosis of multibacillary leprosy demonstrated that in the group that developed reaction (T1R) in the future there was a downregulation of autophagy associated with the overexpression of TLR2 and MLST8. The autophagy impairment in T1R group was associated with increased expression of NLRP3, caspase-1 (p10) and IL-1β production. In addition, analysis of IL-1β production in serum from multibacillary patients demonstrated that patients who developed reversal reaction have significantly increased concentrations of IL-1β at diagnosis, suggesting that the pattern of innate immune responses could predict the reactional episode outcome. In vitro analysis demonstrated that the blockade of autophagy with 3-methyladenine (3-MA) in Mycobacterium leprae-stimulated human primary monocytes increased NLRP3 specks and it was associated with an increase of IL-1β and IL-6 production. Together, our data suggest an important role for autophagy in multibacillary leprosy patients to avoid exacerbated inflammasome activation and the onset of reversal reaction.